Management of biodiesel wastewater by the combined processes of chemical recovery and electrochemical treatment - Jaruwat, Pattaraluk; Kongjao, Sangkorn; Hunsom, Mali (Energy conversion and management, 2010)
A two stage management of raw biodiesel wastewater was carried out at a laboratory scale and ambient temperature. In the first step, biodiesel was chemically recovered from the wastewater using sulphuric acid as a proton donor with subsequent natural phase separation. Biodiesel was recovered from the raw biodiesel wastewater, in this case at 6–7% (w/w). In the second stage, the aqueous phase discharged from the first stage was supplemented with sodium chloride to 0.061 M and subject to electro-oxidation using a Ti/RuO 2 electrode. The combined treatment completely removed COD and oil and grease, and reduced BOD levels by more than 95%. The rate of removal of all three pollutants fitted a pseudo-first-order rate kinetics with oil and grease removal being approximately 8–16- and 2–7-fold faster than BOD and COD removal, respectively.